Linking workplace burnout theories to the project management discipline. Issue 1 (5th March 2018) - Jugdev, Kam; Mathur, Gita; Cook, Christian
Abstract : Purpose: Given the demanding and stressful nature of project work, with a view to explore established concepts of burnout within the project management context, the purpose of this paper is to examine two instruments: the Maslach Burnout Inventory (MBI) and the Areas of Worklife Survey (AWS). Since there is a paucity of literature in project management anchored within the MBI and the Areas of Worklife Survey (AWS), this paper proposes a high-level model on burnout in project management, drawing on the literature underlying these two instruments. Design/methodology/approach: Using a conceptual approach, the paper reviews the social psychology literature on burnout and then the narrow stream of literature on burnout in project management. The paper develops and proposes a conceptual model as a foundation to explore the links between the determinants of project manager burnout/engagement and turnover/retention. Findings: This paper contributes to an improved understanding of the determinants of project manager burnout, engagement, turnover, and retention. Practical implications: The driver for this research is to contribute to the emerging literature on burnout in project management and strategies to help improve engagement and retention of project managers in the discipline – specifically, their tenure in organizations and/or the profession. Originality/value: This paper contributes to the topic of burnout in the project management context. An improved understanding of the stressors in project management contexts, and the mechanisms to mitigate the stress, can add to our understanding of project manager well-being, engagement and retention, improved project success, and healthier work environments.